ANALISIS KRITIS AKSES DAN EKSKLUSI DALAM REGULASI KEHUTANAN UNDANG-UNDANG NOMOR 41 TAHUN 1999 TENTANG KEHUTANAN - Suwarno, Eno; Harahap, Irawan (ANDREW Law Journal, 2025)
This study aims to analyze Law Number 41 of 1999 on Forestry using the access theory developed by Ribot and Peluso. The focus of the analysis is directed at key articles that govern authority, classification, licensing, and law enforcement in forest management in Indonesia. The method employed is normative legal research using content analysis techniques applied to legal documents and scholarly literature. The results show that the state is not only a legal actor that regulates access through law, but also actively produces access through institutional structures, administrative procedures, and exclusive power relations. The provisions of Law No. 41/1999 predominantly facilitate access for capital-intensive actors such as corporations and state institutions, while customary and local communities face structural and legal barriers in obtaining benefits from forest resources. This study concludes that the Forestry Law is centralistic in nature and does not adequately ensure access justice for vulnerable groups. Therefore, a reformulation of the regulation is needed to be more inclusive and decentralized, with formal recognition of community-based access arrangements.